Cultural worldviews and waste sorting among urban Chinese dwellers: the mediating role of environmental risk perception - Cai, Lin; Li, Qingjun; Wan, Erya; Luo, Menglin; Tao, Siwen (Frontiers in Public Health, 2024)
Objective Waste sorting has received considerable attention in recent decades. However, research on the mechanisms underlying the relationships among cultural worldview, environmental risk perception, and waste sorting is rather scarce. This study aims to explore the cultural worldviews, environmental risk perception, and waste sorting among urban Chinese and their mechanisms. Methods This was a cross-sectional study involving 744 urban Chinese residents (371 men and 373 women). A questionnaire was utilized to measure cultural worldviews, environmental risk perception, and waste sorting. Pearson correlation analysis and structural equation modeling were used to examine the relationship between cultural worldviews, perceptions of environmental risk, and waste sorting. Results Waste sorting had a relatively insignificant negative relationship with fatalism and individualism. The correlation between environmental risk perception and cultural worldviews was negative except for egalitarianism, and the correlation between hierarchy and environmental risk perception was higher than the others, while individualism was higher than fatalism. Heightened environmental risk perception mediates the relationship between egalitarianism and waste sorting. Reduced environmental risk perception mediates the relationship between hierarchy and waste sorting, and mediates the relationship between individualism and waste sorting. Conclusion These new findings provide initial support for the mediating role of environmental risk perception in the relationship between cultural worldviews and waste sorting. Both theoretical and practical implications for understanding the psychological mechanisms of waste sorting are discussed.